89.4k views
0 votes
What is equivalent to the polynomial (4x+3)(3x-8)

2 Answers

2 votes


= > (4x + 3)(3x - 8) \\ \\ = > 4x * 3x - 4x * 8 + 3x * 3 - 8 * 3 \\ \\ = > 12 {x}^(2) - 32x + 9x - 24 \\ \\ = > 12 {x}^(2) - 23x - 24
User Hbas
by
5.9k points
1 vote
The equivalent polynomial is 12x^2 -23x - 24.

You can get this by multiplying the two parenthesis by each other.

First start by multiplying the two front numbers:
4x * 3x = 12x^2

Then multiply the outermost numbers:
4x * -8 = -32x

Then multiply the innermost numbers:
3x * 3 = 9x

Then multiply the last numbers:
3* -8 = -24

Now combine all of them to get the above polynomial.
User Shumon Saha
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.